2015
DOI: 10.1177/1740774515571139
|View full text |Cite
|
Sign up to set email alerts
|

Simplification improves understanding of informed consent information in clinical trials regardless of health literacy level

Abstract: Simplified informed consent was effective in enhancing participant's subjective and objective understanding regardless of health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Studies have found that use of a simplified consent form—one using figures and plain language—can improve understanding (Dunn & Jeste, 2001; Kim & Kim, 2015). Others have found that an iterative process of assessing understanding, identifying areas of misunderstanding, and providing corrective feedback can lead to significant improvements in the understanding and appreciation of information (DuBois, Bante, & Hadley, 2011; Nishimura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that use of a simplified consent form—one using figures and plain language—can improve understanding (Dunn & Jeste, 2001; Kim & Kim, 2015). Others have found that an iterative process of assessing understanding, identifying areas of misunderstanding, and providing corrective feedback can lead to significant improvements in the understanding and appreciation of information (DuBois, Bante, & Hadley, 2011; Nishimura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Educational research demonstrates that information perceived as attractive increases its potential and readability [ 10 , 20 ]. Plain language, short sentences, diagrams, pictures and bullet points have also recently in a randomized study been shown to effectively enhance understanding of consent forms irrespective of health literacy level [ 21 ]. Collaboration between investigators and patient representatives has been suggested to improve participant comprehension and satisfaction [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on ethical CT presentation highlights the need to enhance patients’ autonomy by meeting ethical obligations and reforming informed consent processes so that they are an ongoing interactive process that prioritizes patients’ privacy as well as creates opportunities for patients to interact with their social network . Understanding how patient's autonomy is enacted is significant to the broader CT participation literature as it can inform efforts that seek to optimize trial enrolment among patients with cancer.…”
Section: Introductionmentioning
confidence: 99%